The impact study of anti-radiation biomass material on partition wall absorption performance / Norhayati Mohamad Noor... [et al.] - Mohamad Noor, Norhayati; Abdullah@ Idris, Hasnain; Taib, Mohd Nasir; Mustapar, Nabila Husna; Mohd Kasim, Linda; Ahmad, Azizah; Mohamat Kasim, Nazirah; Ismail, Noor Azila (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
With the increasing public concern over radiation exposure and its potential health risks, exploring practical solutions for mitigating radiation in various environments is essential. This study aims to raise awareness about radiation-related issues by investigating the impact of anti-radiation biomass material on the reflectivity performance of partition walls. By incorporating this biomaterial into partition walls, we examine how radiation absorption capabilities can be improved, enhancing overall radiation safety. The process entails combining the biomass material, Palm Oil Fuel Ash (POFA), cement, aluminum, and water in the proper ratios to create a composite material. The combined material is subsequently shaped into partition walls. The anti-radiation biomass partition wall's reflectivity performance was measured using the Naval Research Laboratory (NRL) Arch free space method, with frequencies between 1 GHz and 12 GHz utilised in this project. The study showed that the anti-radiation biomass partition wall containing 35% POFA demonstrated the best reflectivity performance.